Aspects of biopharmaceuticals extraction from Rosa canina and Crataegus monogyna micromycetes - Ukrainska, Anna; Andrianova, Tatiana (Problems of Environmental Biotechnology, 2021)
The plant material of Crataegus and Rosa species is applied in the composition of numerous medicinal preparations for improving the function of cardiovascular and digestive systems, as well as in tinctures, phytocompositions and food supplements. Fungi associated with those plants gain more attention as they may serve as a source of new important biopharmaceuticals. Preliminary phytochemical analysis of Rosa canina and Crataegus monogyna plants was carried out for getting the information on bioactive compounds present in sampled material for subsequent comparison with available fungal metabolites. The next stage included isolation of fungi associated with studied plant species by standard mycological protocols. Species of Microsphaeropsis olivacea and Alternaria alternata were characteristic for leaves and fruits of the common hawthorn, and Aspergillus terreus and Diplocarpon rosae were isolated from the dog rose. Further cultivation and testing of isolates on the presence of biologically active compounds and comparison of their content with results of phytochemical analysis are under the consideration. The preliminary study supports the view that some plants of the family Rosaceae and their associated fungi could be a potent source of biologically active substances.